1988
DOI: 10.1159/000125066
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Receptors in Discrete Brain Areas of the Male Rat

Abstract: The distribution of melatonin receptors in six discrete brain areas of mature (3–4 months old) and aged (>24 months old) male rats was recorded every 4 h during a 24-hour light: dark cycle (L:D 14:10 h). I25I-melatonin was used as a melatonin receptor probe. In the mature animals, specific binding of 125I-melatonin was found in all brain areas investigated, i.e. hypothalamus, medulla pons, hippocampus, cerebellum, parietal cortex and striatum. The density of 125I-melatonin-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Antioxidative stress activity in cerebellar tissue and granular cerebellum cells (Mason et al, 1999) and inhibition of granule cells apoptosis (Persengiev, 2001) were demonstrated. Melatonin membrane receptors were identified in rat and human cerebellum by binding techniques (Laudon et al, 1988;Al-Ghoul et al, 1998); however, melatonin function on cerebellar neurons is still poorly understood.…”
mentioning
confidence: 99%
“…Antioxidative stress activity in cerebellar tissue and granular cerebellum cells (Mason et al, 1999) and inhibition of granule cells apoptosis (Persengiev, 2001) were demonstrated. Melatonin membrane receptors were identified in rat and human cerebellum by binding techniques (Laudon et al, 1988;Al-Ghoul et al, 1998); however, melatonin function on cerebellar neurons is still poorly understood.…”
mentioning
confidence: 99%
“…The reduced expression of MT2 melatonin receptor in hippocampal region of Alzheimer's patients was also mentioned 52 . Further age-related lowering in the density of melatonin binding sites was reported in discrete hypothalamic and hippocampal region of rat brain 33 . Declining expression of melatonin receptors with age in caudal artery of hypertensive rats was also reported 53 .…”
Section: Discussionmentioning
confidence: 83%
“…Melatonin also helps to inhibited lipid peroxidation stimulated by fenton in the thyroid gland 28 . An age-related decline in melatonin receptor binding sites in several tissues of different species including the rat, Syrian hamster and mice supra chiasmatic nucleus (SCN), rat brain [32][33][34] suggested declined melatonin activity in those tissues during aging. In thyroid gland melatonin receptors binding sites were also reported but till date age related patterns of melatonin receptor proteins expression was unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Dax and Sugden [9] reported that reduced serum melatonin level and pineal melatonin level in the rat refl ected a decreased ability of the pineal gland to synthesize melatonin. There was also an age-related reduction in density of melatonin-binding sites in the parietal cortex, hippocampus and medulla pons and a less conspicuous decrease in cerebellum and striatum [10] . Sharma et al [11] reported that plasma melatonin level declined with aging in humans.…”
Section: Introductionmentioning
confidence: 91%